2017
DOI: 10.5194/bg-14-2611-2017
|View full text |Cite
|
Sign up to set email alerts
|

Flooding-related increases in CO<sub>2</sub> and N<sub>2</sub>O emissions from a temperate coastal grassland ecosystem

Abstract: Abstract. Given their increasing trend in Europe, an understanding of the role that flooding events play in carbon (C) and nitrogen (N) cycling and greenhouse gas (GHG) emissions will be important for improved assessments of local and regional GHG budgets. This study presents the results of an analysis of the CO 2 and N 2 O fluxes from a coastal grassland ecosystem affected by episodic flooding that was of either a relatively short (SFS) or long (LFS) duration. Compared to the SFS, the annual CO 2 and N 2 O em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Marín-Muñiz et al (2015) concluded that the Eh plays a vital role in GHG emissions in coastal wetlands. However, we found that the daily mean soil Eh had only a weak positive correlation with daily CO 2 emissions (r = .21) and similar to the results found by Gebremichael et al (2017). Overall, regarding the relationship between the monthly average soil Eh at −30 cm and CO 2 fluxes, the soil Eh may help to interpret the dominant CO 2 flux from aerobic and anaerobic respiration, but this still needs to be investigated in further studies.…”
Section: Soil Respirationsupporting
confidence: 83%
“…Marín-Muñiz et al (2015) concluded that the Eh plays a vital role in GHG emissions in coastal wetlands. However, we found that the daily mean soil Eh had only a weak positive correlation with daily CO 2 emissions (r = .21) and similar to the results found by Gebremichael et al (2017). Overall, regarding the relationship between the monthly average soil Eh at −30 cm and CO 2 fluxes, the soil Eh may help to interpret the dominant CO 2 flux from aerobic and anaerobic respiration, but this still needs to be investigated in further studies.…”
Section: Soil Respirationsupporting
confidence: 83%
“…Finally, water delivery was recently demonstrated to also contribute to differences in N 2 O emissions from irrigated fields [97]. By comparing flood irrigation to sprinkler and drip irrigation, researchers determined that the hydrologic forms (irrigation or flooding frequency, timing, and duration) will cause contrasting GHG emission patterns [98]. Specifically, large volumes of soil pores are water-filled completely and simultaneously during furrow or flood irrigation, which leads to a singular large pulse in N 2 O release from wetted soils; whereas low volume methods, such as sprinkler and drip irrigation, leave a large volume of unfilled pores or partially filled pores, causing more variable and generally less intense pulses of N 2 O emissions [96].…”
Section: N 2 O Emissions and Irrigation Treatmentsmentioning
confidence: 99%
“…While plant invasions may directly or indirectly facilitate GHG emissions, this may also be impacted by growth under waterlogged conditions. High water levels can have complex effects on soil biogeochemical and microbial processes that lead to modifications in soil GHG fluxes [21]. Whilst flooding-related increases in plant-mediated N 2 O emissions may be dependent on nitrate levels [19,22], this could also be related to the increased availability of labile carbon due to the increased decomposition of plant roots [9,23] and/or the extent of rhizosphere oxidation [24].…”
Section: Introductionmentioning
confidence: 99%